Debt/Equity Swaps. (IMF Working Papers; Working Paper ;, 1988)
This paper describes the development of debt/equity swaps in the years following the emergence of the international debt crisis. It discusses some of the possible advantages and disadvantages offered by such swaps to three groups of participants--the commercial banks, the investing companies, and the indebted countries. It also provides an analysis of how these swaps are treated in the balance of payments accounts of an indebted country and discusses their possible effects on that country's money supply, foreign exchange rate and economic growth. The paper concludes that debt/equity swaps can help to make a country's debt burden more manageable and can contribute to economic growth, but only to a limited extent.